Possible doubling of road traffic injury burden in Pakistan: findings from a population-based survey in 2013–2014. (September 2017) - Bhatti, J.A.; Rafique, I.; Azad, A.; Hamid, M.A.; Saqib, M.A.N.; Qureshi, H.
Highlights: A 1997 survey showed annual incidence of 15 traffic injuries per 1000 population in Pakistan. Our population-based survey analysis showed doubling of traffic injury burden in Pakistan in 2012–2013. This public health problem disproportionately affected working men. Findings imply need for improving traffic injury interventions in Pakistan.